2023
DOI: 10.1111/ddg.15159
|View full text |Cite
|
Sign up to set email alerts
|

Itch, sleep loss, depressive symptoms, fatigue, and productivity loss in patients with moderate‐to‐severe atopic dermatitis: Analyses of TREATgermany registry data

Abstract: SummaryBackgroundTREATgermany is a multicenter registry including patients with moderate‐to‐severe atopic dermatitis (AD) from currently 74 study centers (university clinics, hospitals and practices) in Germany. As of August 31, 2021, 1,230 adult patients were enrolled.MethodsIn TREATgermany, patients and physicians fill in questionnaires pertaining to symptoms, disease severity, quality of life, depressiveness, and fatigue. In particular, limitations in work performance are assessed using the Work Limitations… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
3
0
1

Year Published

2024
2024
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 72 publications
0
3
0
1
Order By: Relevance
“…For example, a multicentre study using TREATgermany registry data analysed the work limitations of 228 employees with atopic dermatitis using the WorkLimitations Questionnaire (WLQ). The data analysis showed that moderate-to-severe AD has a negative impact on work productivity [55].…”
Section: School Performancementioning
confidence: 97%
“…For example, a multicentre study using TREATgermany registry data analysed the work limitations of 228 employees with atopic dermatitis using the WorkLimitations Questionnaire (WLQ). The data analysis showed that moderate-to-severe AD has a negative impact on work productivity [55].…”
Section: School Performancementioning
confidence: 97%
“…Patienten mit chronisch-entzündlichen Hauterkrankungen leiden unter Schlafstörungen und Müdigkeit. [1][2][3][4][5] Die Schlafqualität hängt vor allem von zwei Schlafphasen ab, die durch diese Erkrankungen beeinträchtigt werden können: Dem REM-Schlaf (Rapid Eye Movement), auch Traumschlaf genannt, der für die Verarbeitung von Sinneseindrücken und die Erholung unerlässlich ist, und dem Tiefschlaf (N3), der für die Gedächtniskonsolidierung und die kognitive Leistungsfähigkeit von grundlegender Bedeutung ist. 6,7 Verschiedene Parameter, wie zum Beispiel ein erhöhtes Körpergewicht, welches das Risiko einer obstruktiven Schlafapnoe (OSAS) erhöht, können sich negativ auf die Schlafqualität auswirken.…”
Section: Introductionunclassified
“…Patients with chronic inflammatory skin diseases suffer from impaired sleep and fatigue 1–5 . Sleep quality is largely dependent on two sleep phases in particular, which may be affected by these diseases: Rapid Eye Movement (REM) sleep, also known as the dream sleep, which is essential for processing of sensory impressions and recovery and deep sleep (N3), which is fundamental for memory consolidation and cognitive performance 6,7 …”
Section: Introductionmentioning
confidence: 99%